Traffic air pollutant exposure, genotoxicity and respiratory health among traffic police officers in the Klang Valley, Malaysia - Awang, Mohd Fairus (2020)
Traffic-related air pollution (TRAP) is one of the most recent environmental pollution issues widely debated and studied throughout the world. Those who work outdoors such as traffic policemen are the most vulnerable to TRAP exposure and increase in health risks. The aim of this study was to determine the level of TRAP exposure that could affect the respiratory health and chromosomal damage among traffic policemen in Klang Valley. A crosssectional comparative study was conducted between traffic policemen (160) and office workers (149) who employed more than one year in the Klang Valley (Kuala Lumpur, Petaling Jaya, Subang Jaya, Serdang, Shah Alam, Klang, Gombak, Ampang, Kajang, Putrajaya, and Sepang). A standard set of questionnaire adapted from American Thoracic Society (ATS) was distributed to respondents to gather information on respiratory health symptoms, history of exposure, and demographic information. Personal and workplace air pollutant exposures to benzene, toluene, ethylbenzene, xylene (BTEX), and particulate matter with diameter ≤ 2.5 μm (PM2.5) were collected during working hours. The lung function status among respondents was assessed using Spirometer H1105 Chest Graph. Meanwhile, chromosomal damage was detected using micronucleus (MN) assays from the respondents’ buccal epithelial cells. The data analysis was performed using Statistical Package for Social Science Version 23 (SPSS Ver. 23). The results showed that the levels of personal and workplace air pollutant exposures to BTEX and PM2.5 (p<0.001), cough symptom (p = 0.018) and MN frequencies (p<0.001) among traffic policemen were significantly higher than among office workers. The present study also found that the FVC, FEV1, FVC% predicted, and FEV1% predicted were significantly lower among traffic policemen compared to office workers. Only PM2.5 showed significant association with cough symptom at p < 0.001. All pollutants measured in this study had significant associations with the abnormality of FVC% predicted and MN frequencies among the respondents. PM2.5 was the most significant pollutant associated with the cough symptom (B= 1.20, p = 0.013, PR = 3.30, 95% CI = 1.29 – 8.44), FVC% predicted abnormality (B = 1.01, p = 0.032, PR = 1.75, 95% CI = 1.01 – 2.45), and FEV1% predicted abnormality (B = 1.07, p = 0.030, PR = 1.67, 95% CI = 1.12 – 2.31) among respondents. Meanwhile, multiple linear regressions showed that the most significant pollutants related to MN frequency were PM2.5 and benzene. The equation model explains that, if PM2.5 level increases by 1 μg/m3 provided that the concentration of benzene unchanged, the MN frequency will increase by 0.018 frequencies and if benzene level increases by 1 μg/m3 and provided that the concentration of PM2.5 unchanged, the MN frequency will increase by 0.013 frequencies. Thus, shows a high risk of developing cancer among traffic policemen. This study has concluded that, exposure to high level of TRAP among traffic policemen can cause higher prevalence of cough symptom, reduced lung function, and increased MN formation compared to office workers. In order to reduce the health effects among traffic policemen, this study suggests that the Malaysian Police Department should monitor TRAP exposure, health inspections for at least once every six months and use face masks while performing duties among traffic policemen.